Relationship between Sleep Quality and Physical Activity: A Crossectional Study in the Elderly Community of Sanden Health Center, Yogyakarta - Indriani; Munandar, Teguh Aris (Infomasi dan Promosi Kesehatan, 2024)
The impact of successful development is the increase in Life Expectancy (UHH) and the elderly population. Aging is characterized by changes in anatomical structure, physiology, and changes in sleep quality. Decreased sleep quality is a frequent problem and can be the cause of cognitive impairment, dementia, and Alzheimer's which affect the quality of life of the elderly. Sleep quality in the elderly is influenced by various factors, including physical health, psychological state, and socioeconomic status. Understanding these factors is crucial to improving the overall well-being of the elderly. This study aimed to identify factors associated with sleep quality in the elderly in Yogyakarta. The cross-sectional study was conducted at the Sanden Health Center, Bantul Yogyakarta. From 269 total population, a sample of 120 elderly was obtained using purposive sampling. Socio-demographic data of the elderly were obtained from questions and answers with respondents, sleep quality, and physical activity, using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the Physical Activities Scale For Elderly (PASE) questionnaire. Anthropometric measurements of data were carried out to determine the BMI of the elderly who were divided into thin, normal, and obese. Data analysis with Chi-Square using SPSS version 24.0. Results: 57 elderly (47.5%) had poor sleep quality and there was a significant relationship between physical activity and sleep quality (p = 0.005). Conclusion: The low sleep quality of the elderly requires the development of community-based health promotion strategies where a supportive environment plays an important role in helping the elderly maintain physical activity levels. Cross-sectoral collaboration is needed; for the government, professionals, academia, media, and private sector to take joint action, to improve the health status of the elderly in the communities where they live.